2013
DOI: 10.4161/hv.26796
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric nanoparticles

Abstract: Nanocarriers with various compositions and biological properties have been extensively applied for in vitro/in vivo drug and gene delivery. The family of nanocarriers includes polymeric nanoparticles, lipid-based carriers (liposomes/micelles), dendrimers, carbon nanotubes, and gold nanoparticles (nanoshells/nanocages). Among different delivery systems, polymeric carriers have several properties such as: easy to synthesize, inexpensive, biocompatible, biodegradable, non-immunogenic, non-toxic, and water soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 227 publications
(92 citation statements)
references
References 73 publications
0
85
1
Order By: Relevance
“…Our studies also showed that the mixture of a plasmid DNA harboring human papillomavirus experiments indicated that the use of PEI600-Tat conjugates with low cytotoxicity was more potent than the two components without chemical linkage [131][132][133][134][135] .…”
Section: Application Of Cationic Polymers In Vaccinationmentioning
confidence: 65%
“…Our studies also showed that the mixture of a plasmid DNA harboring human papillomavirus experiments indicated that the use of PEI600-Tat conjugates with low cytotoxicity was more potent than the two components without chemical linkage [131][132][133][134][135] .…”
Section: Application Of Cationic Polymers In Vaccinationmentioning
confidence: 65%
“…liposomes, [16] colloidal polymers and nano-particles. [1719] The biotechnologies for using these materials as safe and effective vaccine carriers have been under study for some time. Still ongoing is the new strategy to develop Leishmania as the first eukaryotic vehicle for vaccine delivery on the basis of their unique properties, e. g. the efficacy of protecting vaccine payload and homing to antigen-presenting cells and their safety by photodynamic inactivation with reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Additionally, these carriers can also be designed as low toxicity systems with suitable physical and chemical structures and specific targeting properties for delivery of cancer vaccines. 11,30 To this end, understanding the interactions between nanomaterials and DCs is important in the field of immunotherapy. It is necessary to consider the properties of NPs in terms of composition, adjuvant activity, size, surface properties to fabricate vaccine delivery carriers.…”
Section: Important Characteristics Of Nanoparticle-based Vaccine Delimentioning
confidence: 99%